smAR2t: a Models at Runtime Architecture to Interact with the Web Of Things using Augmented Reality - Bezerra, Jagni Dasa Horta; de Souza, Cidcley Teixeira (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
The Internet of Things has a high heterogeneity of devices, cloud services, communication protocols and comprises different research and development areas. This implies in ease-of-use problems for users who interact with high-density smart environments using common interface solutions, demanding specific applications for each device. There are also situations where things change their locations and networks, bringing even more complexity to this scenery. A great number of recent researches point Augmented Reality(AR) as an interface solution that is capable of providing rich user experiences for high-density IoT environments. W3C's Web of Things standards(WoT) are proving to be a feasible solution for IoT's heterogeneity issues by using well-known web protocols and the Thing Description(TD) formal model. This paper's goal is to propose an architecture called smAR2t that integrates these solutions by managing mobility, heterogeneity and high-density of smart environments, allowing users to browse their surroundings with AR and to interact with things seamlessly according to each of their TDs. This could be done by: representing TDs in a higher level of abstraction with models; transforming these models at runtime to reflect real-time interactions and behaviors; updating an auto-generated AR interface according to these models.